N-acetyl cysteine versus chlorhexidine mouthwashes in prevention and treatment of experimental gingivitis: A randomized, triple-blind, placebo-controlled clinical trial - Al-Kamel, Ahlam; Al-Hajj, Wadhah Abdulnaser; Halboub, Esam; Abdulrab, Saleem; Al-Tahami, Khaled; Al-Hebshi, Nezar Noor (Springer Nature, 2019)
Objectives To compare the efficacy of N-acetyl cysteine (NAC) mouthwash with chlorhexidine (CHX) in prevention and treatment of experimental gingivitis Materials and methods Sixty subjects were assigned randomly and blindly into one of three equal groups: NAC, CHX, or placebo group. The study was conducted in two stages: preventive and treatment substudies. Professional prophylaxis was performed ahead of starting the preventive substudy. Then, the subjects were instructed to stop oral hygiene practices and begin rinsing twice/day with 15 ml of the assigned mouthwash (1.25% NAC, 0.2% CHX, or inert base). Plaque index (PI), gingival index (GI), and papillary bleeding index (PBI) were measured at baseline, 7, 14, and 21 days. The treatment substudy started on day 21 in which the subjects in the placebo group (now with established experimental gingivitis) were assigned to NAC (n?=?10) or CHX (n?=?10); the abovementioned indices were measured at 28 and 35 days. Efficacy of these interventions was compared. Results All groups accumulated plaque and developed some degree of gingivitis: full-blown in the placebo group and remarkably mild in the CHX group. NAC had slight preventive properties at days 14 and 21. In the treatment substudy, CHX was associated with remarkable reduction in plaque and gingivitis while NAC resulted in insignificant reductions. Conclusions 1.25% NAC is marginally effective in prevention and treatment of experimental gingivitis. Clinical relevance When compared with the placebo, NAC showed promising preventive and treatment effects of gingivitis that deserve further development and studies.